A Program for Preparing Teachers To Serve Handicapped Migrant Students in Rural Areas - Joyce, Bonnie G. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
Although children of migrant workers tend to have low educational achievement, there is a surprising lack of data concerning educational challenges faced by handicapped migrant children. It is often a teacher's advocacy that results in a student's enrollment in special education services. This paper describes a Florida program for training special educators as advocates for handicapped migrant children. The training program provides instruction in competencies for teachers serving mild and moderately handicapped migrant students in rural areas, and includes components in other related fields. Course content is divided into three areas of competency development: (1) assessment of academic performance, behavior, and vocational interest; (2) intervention through individualized instruction and transition-to-work plans; and (3) cultural understanding. The effectiveness of the training program is evaluated through Q-sort methodology coupled with frequency data. A list of the training program's 25 competencies is included. (TES)
ERIC Note: In: Education and the Changing Rural Community: Anticipating the 21st Century. Proceedings of the 1989 ACRES/NRSSC Symposium. See RC 017 257.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Education; Child Advocacy; Disabilities; Helping Relationship; Higher Education; Inservice Teacher Education; Migrant Children; Migrant Education; Rural Education; Special Education; Special Education Teachers; Teacher Education Programs; Florida; Speeches/Meeting Papers; Reports, Descriptive